Cactaceae endémicas del Perú - Arakaki, Mónica (2006)
The Cactaceae are represented in Peru by 43 genera and nearly 250 species (Brako & Zarucchi, 1993; Ulloa Ulloa et al., 2004), mostly erect-columnar or sprawling cactus. Here we recognize 1999 endemic taxa in 32 genera. Six genera-Calymnanthium, Lasiocereus, Matucana, Mila, Oroya and Pygmaeocereus- are endemic to Peru. This family requires methodic efforts to increase the number of vouchers in national herbaria, as well as evaluations of the populations, habitats, taxonomy and systematics of these taxa. Most endemic taxa are found in the Desert Shrubland and Mesoandean regions, from sea level to 4000 m elevation. We applied IUCN categories and criteria to 58 taxa. Fifteen endemic taxa have been recorded in the Peruvian parks system.